New frontier of gene therapy: Tecelra’s promise for metastatic synovial sarcoma - Amjad, Hammad; Muhammad Farhan; Abid, Mobeen (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Synovial sarcoma (SS) is a sporadic, invasive soft tissue sarcoma with epithelial differentiation, primarily affecting young adults and adolescents. It constitutes about 10% of soft tissue sarcomas. The five-year survival rate for SS is 50% to 60%, and five-year metastasis-free survival rate is 40% to 60%. It grows slowly, which can delay diagnosis, and often metastasises to the lungs. Patients clinically present with a deep, multinodular mass that has been present for years, accompanied by local pain and tenderness. However, symptoms vary upon tumour location. Magnetic resonance imaging is preferred for diagnosis and staging; however, Positron emission tomography/Computed tomography scans are also used to check for metastases[1]. Current treatments include surgery for localised tumours, radiotherapy and more generally standard treatment is anthracycline-based chemotherapy. At the same time, clinical trials on engineered T-cell receptor gene therapy for either confirmation or testing have taken place and are still ongoing[2]. Gene therapy involves the transfer of a genetic material into patient’s cells and works by either enabling or inhibiting expression of the target gene or by modifying it. In contrast, chemotherapy effectively kills or inhibits cancer cells and possesses the ability to destroy healthy cells, making it nonspecific and with grave side effects such as immunosuppression. Until recently, the FDA has approved Tecelra with the active agent, afamitresgene autoleucel (afami-cel), a one-of-a-kind first-ever gene therapy for metastatic SS[3]. It consists of the patient’s own human leukocyte antigen-restricted autologous T cells engineered to express a receptor with enhanced affinity and specificity for the MAGE-A4 peptide. This antigen triggers the immune system and is expressed by the tumour cells in SS. Phase I trial conducted with the primary objective of evaluating the safety, tolerability and clinical activity of afami-cel revealed that, out of 16 pre-treated metastatic SS patients, seven partially responded to afami-cel infusion representing an overall response rate (ORR) of 44%. At the same time eight showed stable disease resulting in 94% disease control rate. Two patients also exhibited significant reduction of pleural metastases, with one patient achieving complete resolution of a pleural metastasis. The sustained decrease in the size of target lesions over several months in some patients after a single infusion of afami-cel indicates that its anti-cancer effects last for a greater period than expected after a single cycle of lymphodepletion (LD) chemotherapy. —Continue